2020
DOI: 10.1021/acs.macromol.0c01665
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable, Recyclable, and Fast Room Temperature Self-Healable Biobased Elastomers Using Polycondensation

Abstract: The substitution of petroleum-based self-healing elastomers with biobased counterparts is crucial to the global sustainable development of the rubber industry, which highly depends on the ease of the synthesis procedure. Herein, we show that highly stretchable, recyclable, and self-healable biobased elastomers were synthesized via condensation polymerization of succinic acid, adipic acid, sebacic acid, and 1,4-butanediol in the presence of a small amount of glycerol as a curing agent and 3,3′-dithiodipropionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 56 publications
2
57
1
Order By: Relevance
“…We hypothesized that a simple and straightforward route to achieve such a system would be by leveraging a solvent-free, ring-opening aminolysis-condensation/crosslinking strategy of renewable ethylene brassylate, 43,44 and the fast disulfide exchange. 4,23,39 The dynamic character of the resulting long-chain PA network was verified by stress relaxation analysis and the material was thermally reprocessable over three grinding-compression molding cycles without deterioration of its properties.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We hypothesized that a simple and straightforward route to achieve such a system would be by leveraging a solvent-free, ring-opening aminolysis-condensation/crosslinking strategy of renewable ethylene brassylate, 43,44 and the fast disulfide exchange. 4,23,39 The dynamic character of the resulting long-chain PA network was verified by stress relaxation analysis and the material was thermally reprocessable over three grinding-compression molding cycles without deterioration of its properties.…”
Section: Introductionmentioning
confidence: 96%
“…Their principle is the activation of exchange reactions between dynamic bonds that overall keep the crosslink density of the network constant, but allow it to flow and rearrange its topology at high temperature. Thus, CANs meld the features of classical thermosets such as chemical resistance and dimensional stability with reprocessability, and in some cases self-healing ability and chemical recycling, [2][3][4][5][6][7] all highly attractive features for many applications. 8 Polyamide (PA) networks have rarely been reported, let alone PA networks with exchangeable bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that aromatic disulfide compounds can undergo disulfide exchange reactions at room temperature 28,29 . The dynamic disulfide bonds are introduced to give polyurethane self‐healing and reprocessing properties, 30–34 but its impact on dynamic mechanical properties has been ignored. The broken of the aromatic disulfide bonds will absorb energy at and above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The main monomeric products separable from these complex organic structures are carboxylic acids and their analogs. These compounds can serve as starting materials for both the chemical and materials industries [8][9][10][11]. The commercial value of organic compounds from oil shale organic matter (kerogen) may be several times higher than that from the current use of oil shale (e.g.…”
Section: Introductionmentioning
confidence: 99%